Identification of anthocyanin and other flavonoids from the green–blue petals of Puya alpestris (Bromeliaceae) and a clarification of their coloration mechanism. (January 2021) - Mizuno, Takayuki; Sugahara, Kohtaro; Tsutsumi, Chie; Iino, Moritoshi; Koi, Satoshi; Noda, Naonobu; Iwashina, Tsukasa
Abstract: To understand the unique green–blue color of Puya alpestris (Bromeliaceae) flowers, we investigated their constituent anthocyanin and related compounds. An anthocyanin, two undescribed flavonols, and two flavones were isolated and identified as delphinidin 3, 3′, 5′-tri- O - β -glucopyranoside, myricetin 3- O -[ α -rhamnopyranosyl-(1 → 6)- β -glucopyranoside]-3′, 5′-di- O - β -glucopyranoside, myricetin 3, 3′, 5′-tri- O - β -glucopyranoside, luteolin 4′- O -glucoside, and apigenin 4′- O -glucoside. Furthermore, the presence of chlorophyll has also been revealed. P. alpestris petals show a gradient color appearance: Green–blue at the tip and blue at the base. This color difference between the tip and base was used to analyze the pigment components underlying the green–blue color expression. It was found that the petal tip contains the anthocyanin, flavonols, flavones, and chlorophyll in high quantities. Furthermore, the pH of petal juice was 6.2 and 5.6 at the tip and base, respectively. In vitro reconstruction revealed the blue color expression occurred via an intermolecular copigmentation between the anthocyanin and flavones, as well as yellow color expression, which was due to an increase in the absorption at 400–450 nm of the flavonols under the higher pH conditions. Furthermore, we found that the petal extract obtaining using 50% acetone containing chlorophyll showed the same absorption spectrum as that observed for the raw petal. These results indicate that the green–blue color of P. alpestris flowers is developed via an intermolecular co-pigmentation of the anthocyanin (delphinidin 3, 3′, 5′-tri- O - β -glucopyranoside) with flavones, such as luteolin 4′- O -glucoside, the yellow color expression of flavonols, such as myricetin 3, 3′, 5′-tri- O -glucoside under relatively high pH conditions in the cell sap, and the presence of chlorophyll. Graphical abstract: Image 1 Highlights: An anthocyanin, two undescribed flavonols, and two flavones have been identified from  Puya alpestris  (Bromeliaceae). The bluing effect of the anthocyanin with flavones was observed using in vitro reconstruction studies. The yellow expression of flavonols under relatively high pH conditions was observed in an aqueous solution. The blue and yellow expression and chlorophyll contribute to the color expression.